Single-sex schistosomiasis: a mini review - Zhong, Haoran; Jin, Yamei (Frontiers in Immunology, 2023)
Schistosomiasis is a neglected tropical disease caused by dioecious blood flukes of the genus Schistosoma and second to malaria as a parasitic disease with significant socio-economic impacts. Mating is essential for maturation of male and female schistosomes and for females to lay of eggs, which are responsible for the pathogenesis and propagation of the life cycle beyond the mammalian host. Single-sex schistosomes, which do not produce viable eggs without mating, have been overlooked given the symptomatic paucity of the single-sex schistosomiasis and limited diagnostic toolkit. Besides, single-sex schistosomes are less sensitive to praziquantel. Therefore, these issues should be considered to achieve the elimination of this infection disease. The aim of this review is to summarize current progress in research of single-sex schistosomes and host-parasite interactions.